Phenanthrene and dihydrophenanthrene derivatives from Dioscorea communis with anticholinesterase, and antioxidant activities. Issue 22 (17th November 2019) - Boudjada, Amina; Touil, Ahmed; Bensouici, Chawki; Bendif, Hamdi; Rhouati, Salah
Abstract: Five phenanthrene and two dihydrophenanthrene derivatives were isolated from the diethyl ether extract of fresh rhizomes of Dioscorea communis (L.), among them a phenanthrentriol1 reported for the first time from Dioscoreaceae family and two dihydrophenanthrene derivatives6 and7 reported also for the first time from Dioscorea species. The structures of isolated compounds were elucidated using UV, IR, 1D-, 2D-NMR, and MS techniques. The anticholinesterase activity of extracts and four compounds was evaluated for the first time against acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) enzymes using Ellman method. Moreover, the antioxidant activity of extracts and three compounds has been investigated using DPPH radical scavenging, ABTS cation radical decolorization, CUPRAC, reducing power and β-carotene bleaching assays. Abstract :